2016
DOI: 10.1007/s00586-016-4627-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of a health questionnaire on back care knowledge in daily life physical activities for adolescent students

Abstract: Purpose The most relevant musculoskeletal problems are related with back health. Study instruments have been designed for adult patient population but not for school-aged children. The aim of this study was to develop and evaluate the psychometric properties of a questionnaire to assess adolescents' level of back care knowledge in daily life physical activities. Methods Participants were 171 adolescents from secondary schools. The questionnaire was made up of 24 questions. A Delphi method was used for test val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
1
26
0
1
Order By: Relevance
“…Some studies, including the studies, done by the research team of current study, reported high prevalence of musculoskeletal pains and effects of some risk factors and predictors on them [ 23 , 24 ]. Some of these predictors are knowledge and beliefs of care for back and spine, posture and ergonomics and other cognitive factors like perceived self-efficacy, perceived benefits, perceived barriers and intention behavior [ 7 , 25 – 28 ]. Thus, in this study, the constructs of Health Belief Model including perceived susceptibility, perceived severity, perceived benefits, perceived barriers and perceived self-efficacy also were employed (22).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, including the studies, done by the research team of current study, reported high prevalence of musculoskeletal pains and effects of some risk factors and predictors on them [ 23 , 24 ]. Some of these predictors are knowledge and beliefs of care for back and spine, posture and ergonomics and other cognitive factors like perceived self-efficacy, perceived benefits, perceived barriers and intention behavior [ 7 , 25 – 28 ]. Thus, in this study, the constructs of Health Belief Model including perceived susceptibility, perceived severity, perceived benefits, perceived barriers and perceived self-efficacy also were employed (22).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized control trials on back health education in school settings demonstrate that educational interventions effectively improve awareness, postural habits, core muscle endurance, and back health in children [13][14][15][16][17][18]. Along this line and to facilitate the evaluation of educational interventions, other studies [19][20][21][22] have focused on elaborating and validating the design of reliable evaluation instruments to assess contents related to back health. The contents addressed by these studies include awareness, postural habits, and back health in the school setting.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal disorders (MSDs), including back pain, are among the most important problems causing excessive absenteeism in the workplace, imposing high economic costs on health care systems, and suffering nearly 540 million people [ 1 5 ]. As described by the World Health Organization (WHO), back pain comprises low back and neck pain (mild, moderate, severe, and most severe).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Spence et al [ 11 ] and Sheldon [ 12 ] introduced written and practical tests to assess pupils’ knowledge and performance with regard to correct lifting techniques among 3th, 5th, 6th, and 8th-grade public-school children. As well, Monfort et al [ 1 ] developed and evaluated the psychometric properties of a health questionnaire on back-care knowledge in daily life physical activities (known as HEBACAKNOW), consisting of 24 items examining levels of back-care knowledge among adolescents. Similarly, Noll et al [ 2 ] designed the Back Pain and Body Posture Evaluation Instrument (BackPEI) for schoolchildren, relevant to the evaluation of back pain and its associated behavior risk factors.…”
Section: Introductionmentioning
confidence: 99%